PELAKSANAAN PEMASARAN DIGITAL DI HOTEL GRAND SUKA PEKANBARU - Wicaksana, Ramli Muhammad; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the implementation of Digital Marketing for the Grand Suka Pekanbaru Riau Hotel. This research uses qualitative methods which are able to explain phenomena through data collection through observation, interviews and documentation. Any data obtained by the author is then collected, processed and explained clearly using language that is easy to understand. The data collection technique is by means of in-depth interviews and the author immediately goes to the hotel to observe the place (observation), then takes data in the form of author documentation. This research uses a descriptive approach where this research explains in detail the implementation of Digital Marketing for the Grand Suka Hotel Pekanbaru Riau. Based on the results of the research that has been carried out, the Digital Marketing Implementation of the Grand Suka Pekanbaru Hotel uses Marketing Theory and Digital Marketing to identify and classify consumers so as to create a product image for consumers and be able to compete well. By creating good and correct marketing implementation and utilizing Digital Technology (Social Media) such as Instagram and YouTube are expected to be able to market and promote the Grand Suka Hotel widely and can benefit from the large number of guests who are interested and come. to stay at the Grand Suka Hotel Pekanbaru Riau. Keywords: Digital Marketing Implementation, Marketing Mix, Hotel.